2016
DOI: 10.1002/jrs.4908
|View full text |Cite
|
Sign up to set email alerts
|

Automatic classification system of Raman spectra applied to pigments analysis

Abstract: Raman spectroscopy is one of the few non-destructive techniques capable of identifying pigments in art works. Raman spectra contain powerful information that can be used to identify unknown compounds and their chemical structures. However, the analysis of spectral data comes with some difficulties and therefore the spectral interpretation is not straightforward. Sometimes, there are very little differences in the spectral data concerning to specific identification objectives, for instance, in polymorphic discr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Binary pigment mixtures were explored by Gonz alez-Vidal et al 23 They used PCA to reduce the size of the dataset (baseline corrected, intensity normalized, interpolated spectra). The reference dataset was composed of 20 inorganic and 31 SOPs.…”
Section: Pca On Raman Spectramentioning
confidence: 99%
“…Binary pigment mixtures were explored by Gonz alez-Vidal et al 23 They used PCA to reduce the size of the dataset (baseline corrected, intensity normalized, interpolated spectra). The reference dataset was composed of 20 inorganic and 31 SOPs.…”
Section: Pca On Raman Spectramentioning
confidence: 99%
“…It should, however, be taken into account that reference spectra are mostly acquired on pure materials, like pigment powders. When compared with paint systems, differences in heat dispersion or fluorescence behaviour may lead to slight differences in the spectra [43,44]. The excitation wavelength and power of the laser can influence the reference spectra too.…”
Section: Interpretation Of Raman Spectramentioning
confidence: 99%
“…Gonzalez‐Vidal co‐workers described an automatic classification system of Raman spectra applied to pigments analysis. Their implemented methodology was used to classify Raman spectra of pigments commonly present in artist's paints in experimental cases, providing reliable and consistent results . Kupka et al described the modeling of red coral ( Corallium rubrum ) and African snail (Helixia aspersa) shell pigments by means of the comparison of measured Raman versus calculated DFT spectra.…”
Section: Art and Archaeologymentioning
confidence: 99%
“…Their implemented methodology was used to classify Raman spectra of pigments commonly present in artist's paints in experimental cases, providing reliable and consistent results. [129] Kupka et al described the modeling of red coral (Corallium rubrum) and African snail (Helixia aspersa) shell pigments by means of the comparison of measured Raman versus calculated DFT spectra. It was concluded that all-trans polyene pigments of red coral and dark parts of African snail shell contain 11-12 and 14 C=C double bond units, respectively; however, Raman spectroscopy cannot produce any clear information on the presence and nature of the end-chain substituents in the studied pigments.…”
Section: Glasses Ivory Resins Porcelain Pottery Bronzes Panesmentioning
confidence: 99%